2015
DOI: 10.1021/acs.nanolett.5b02129
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-Driven Crystallization Behavior in DNA-Mediated Nanoparticle Assembly

Abstract: Herein, we report an example of entropy-driven crystallization behavior in DNA-nanoparticle superlattice assembly, marking a divergence from the well-established enthalpic driving force of maximizing nearest-neighbor hybridization connections. Such behavior is manifested in the observation of a non-close-packed, body-centered cubic (bcc) superlattice when using a system with self-complementary DNA linkers that would be predicted to form a close-packed, face-centered cubic (fcc) structure based solely on enthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 39 publications
2
44
0
Order By: Relevance
“…These simulations build upon previous work that has been shown to accurately predict the DNA-mediated crystallization behavior of spherical particles (23,(31)(32)(33)(34)(35); however, the broken symmetry of polyhedra requires additional considerations (SI Discussion and Tables S5-S7). Although the experimentally investigated samples are too large to model exactly, SA and D were scaled to a computationally accessible size regime in a manner consistent with experiments, and DNA density was set based on experiments (Fig.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…These simulations build upon previous work that has been shown to accurately predict the DNA-mediated crystallization behavior of spherical particles (23,(31)(32)(33)(34)(35); however, the broken symmetry of polyhedra requires additional considerations (SI Discussion and Tables S5-S7). Although the experimentally investigated samples are too large to model exactly, SA and D were scaled to a computationally accessible size regime in a manner consistent with experiments, and DNA density was set based on experiments (Fig.…”
mentioning
confidence: 72%
“…Calculations show that the observed transitions originate from ligand-based entropic and enthalpic contributions. In particular, an increased average inter-DNA spacing on the particle and lattice compression both indicate a wider range of less-oriented DNA states, and thus an increased free volume accessible to each DNA sticky end (32). This flexibility also allows for more DNA connections to be made between particles, as indicated by a greater F.…”
mentioning
confidence: 99%
“…Stabilization of floppy crystals can be due to either enthalpy or entropy. For a single component system of DNA-coated nanoparticles [26], including the configurational entropy of the linkers in the effective potential (as adopted in this work), the b.c.c. crystal is believed to be favored over the f.c.c.…”
mentioning
confidence: 99%
“…Bond strength can even be postsynthetically increased through the use of ruthenium coordination complexes, ethidium bromide, or silver ion intercalators . While dsDNA is relatively stiff, the flexibility of DNA strands between PAEs can be independently tuned by incorporating ssDNA bases or polyethylene glycol “flexors” to affect crystallization ability and quality or alter the entropic penalty associated with PAE bond formation, which can result in alterations to PAE superlattice structure …”
Section: Versatility In the Pae Constructmentioning
confidence: 99%
“…While the predominant driving force that dictated the thermodynamically favorable lattice structure for a given set of PAEs was initially discovered to be almost entirely an enthalpic maximization of DNA binding, it was later found that entropic effects could be increased with flexible DNA linkers, thereby inducing self‐complementary PAEs to form a bcc lattice even though this structure represents a lower packing density than the prior fcc structures that had been obtained in unary systems . Making the core–core interactions appreciable in scale, one study created the binary phase isostructural to sodium‐thallium (NaTl) .…”
Section: Versatility In the Pae Constructmentioning
confidence: 99%